Beyond the Visible and Below the Peel: How UV-B Radiation Influences the Phenolic Profile in the Pulp of Peach Fruit. A Biochemical and Molecular Study - Santin, Marco; Castagna, Antonella; Miras-Moreno, Begoña; Rocchetti, Gabriele; Lucini, Luigi; Hauser, Marie-Theres; Ranieri, Annamaria (Frontiers in Plant Science, 2020)
In the last decades, UV-B radiation has attracted attention due to its potential to increase nutraceutical values of fruit and vegetables, especially by inducing the accumulation of phenolics in a structure-dependent way. However, most current studies have investigated the UV-B-driven changes only in the peel or focusing on individual phenolic classes. Adopting an “-omics” approach, this work aimed to deepen the knowledge about the effects of UV-B radiation on the phenolic profile in the pulp of peach fruit. Based on these considerations, melting flesh yellow peaches (Prunus persica L., cv. Fairtime) were subjected to either a 10-min or 60-min UV-B treatment (1.39 kJ m−2 and 8.33 kJ m−2, respectively), and sampled at different time points from the exposure. A UHPLC-ESI/QTOF-MS analysis coupled with a phenolics-specific database for the annotation of compounds and a multivariate discriminant analysis revealed a marked effect of UV-B radiation on the phenolic profiles of peach pulp. Particularly, a general, transient increase was observed after 24 h from the irradiation, especially for flavanols, flavonols, and flavones. Such behaviour diverges from what was observed in the peel, where an overall increase of phenolics was observed after 36 h from the irradiation. Concerning the flavonols in the pulp, UV-B exposure stimulated a specific accumulation of isorhamnetin and kaempferol derivatives, with variations imposed by the different sugar moiety bound. Anthocyanins, which were the second most abundant flavonoid group after flavonols, displayed a general decrease after 36 h that was not attributable to specific molecules. The UV-B treatments also increased the glycoside/aglycone ratio of flavonols and anthocyanins after 24 h, by increasing the glycoside concentration of both, flavonols and anthocyanins, and decreasing the aglycone concentration of anthocyanins. In support of the biochemical results, targeted gene expression analysis by RT-qPCR revealed an UV-B-induced activation of many genes involved in the flavonoid pathway, e.g. CHS, F3H, F3’H, DFR, as well as some MYB transcription factors and few genes involved in the UV-B perception. Generally, all the flavonoid-related and MYB genes showed a transient UV-B dose-dependent activation after 6 h from the irradiation, similarly to what was observed in the peel.